Results of training on COVID-19. University of Medical Sciences of Cienfuegos, 2020 - Anay de la Caridad Núñez Herrera; Manuel Fernández Urquiza; Yamirka González Puerto; Carlos Ricardo Gaimetea Castillo; Yanet Rojas Rodríguez; Tania Elena López Otero (Medisur)
Foundation: COVID 19 has become a pandemic. As a new disease, the scientific community is studying it. Health professionals and people in general need to know everything related to this condition, in order to face it as well as possible. Objective: to describe the results of the training developed by the Post graduate Department of the Cienfuegos University of Medical Sciences on COVID-19. Methods: descriptive study on training actions conducted from February to April 2020, in a universe of 147 677 health professionals and other areas, as well as students, management personnel, self-employed and members of mass organizations. It was carried out in stages, according to indications received by the Ministry of Public Health. Results: out of the universe, a percentage of 8.78% was trained, highlighting the second period with a total of 108,901. Some of the topics taught were: biosecurity, intensive care, mechanical ventilation, rapid tests and assimilation - adherence to the different action protocols versions. Conclusion: Cienfuegos has a high number of trained personnel, in different areas of knowledge, to face COVID-19, which allows having a more educated and prepared population.